STRATEGI KOMUNIKASI RIAU TOURISM BOARD DALAM MEMPROMOSIKAN PARIWISATA DI PROVINSI RIAU - Pricilla, Monica; Wirman, Welly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Tourist visits to the Riau province both foreign and domestic each year has increased but has not reached the desired target by the Riau provincial government of 60,000 tourists in 2013. Riau provincial government for several years is quite heavily promoting tourism through cooperation with Riau Tourism Board for example by initiated an event called Visit Riau, publish tourism magazine named Visit Riau and follow the promotion of tourism to the various countries to promote tourism in Riau province. The purpose of this study is to determine the communication target recognition, assessment purposes communication message, the selection of communication media and the role of communicators in the communications made by Riau Tourism Board to promote tourism in the Riau Province. This study is a qualitative research that do not use statistical analysis procedures. All information of the study was obtained from informants as many as 5 people from Riau Tourism Board officials namely (Head, Deputy Head, Secretary and staff), using purposive sampling. The study states that the identification of the target audience is divided into domestic and foreign tourists. Assessment destination communication message, Riau Tourism Board to use the media that emphasizes the content of the message, in form of : a) the Malay Cultural Festival, Riau Expo and Expo Pekanbaru, Riau Visit tourism and bulletins to get the attention and interest of tourists to come to visit, perform dances and other art of Riau Culture (visualization), and invites businesses like hotel owners, travel agents to participate in the increase of tourist visits (action). Communication media used by Riau Tourism Board are through: Pekanbaru Riau Expo and Expo as well as exhibitions and expo outside Riau Province such as Jakarta Fair, Medan Fair, arts and cultural performances such as Cultural Festival. Using printed mass media such as Visit Riau bulletin, Indonesia Wonderful Bulletin and Pekanbaru Tourism Enchantment. Communicators in delivering campaign is the chairman and board Riau Tourism Board.Keywords: Strategy, Communications, Tourism